Cosmetic Gynecology: Present and Future Perspectives - Mishra, Prabhu Chandra; Mihai, Diana; Khurana, Nidhi; Jabbar, Manar (International Journal of Innovative Research in Medical Science, 2021)
Postmenopausal women and events like childbirth, and aging may cause structural and functional changes in women genitalia. The arising indications do not only cause psychological distress to women but negatively affect the sexual well-being and deteriorate the quality of their lives. Regenerative/ cosmetic gynecology procedures enable women to treat the functionality issues and modify the physical structure of vagina. This review discusses the latest developments in this field with regards to various kinds of procedures that are available, particularly the use of energy-based devices, and adipose tissue derived stem cells therapy for fat grafting which have revolutionized the regenerative gynecology procedures. These offer non-invasive modalities to treat the conditions like urinary incontinence among others which occur in high prevalence among women. Despite the advancements made in this field, it lacks regulatory guidelines and standardized procedures which imposes one of the biggest challenges of the field. Alongside, we have documented a procedure called Intimacell® which has been standardized for fat grafting procedures in vulvovaginal region.